2014
DOI: 10.1371/journal.pone.0091036
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Reflects the Natural History of Physiological Development in Healthy Children and Is Not Associated with Quality of Life

Abstract: BackgroundQuality of life (QoL), being the sum expression of diverse influencing factors, is not easy to determine. A clinically relevant option would be to identify and measure quality of life on the basis of physiological parameters which correlate plausibly and statistically with psychometrically measured QoL. Analysis of heart rate variability (HRV) offers readily measurable physiological parameters which could be of use here. A correlation of HRV with both course of disease and QoL has been reported in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…The physiologic consequences of chronic illness could influence the relationship observed between HRQOL and HRV. Few studies have focused on healthy individuals in order to avoid overestimation of the association between HRQOL and HRV, but these studies’ results were inconsistent [ 11 , 27 , 28 ]. Furthermore, these studies have the limitation of lacking a procedure to control the physical and psychiatric conditions that can confound HRV profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The physiologic consequences of chronic illness could influence the relationship observed between HRQOL and HRV. Few studies have focused on healthy individuals in order to avoid overestimation of the association between HRQOL and HRV, but these studies’ results were inconsistent [ 11 , 27 , 28 ]. Furthermore, these studies have the limitation of lacking a procedure to control the physical and psychiatric conditions that can confound HRV profiles.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has been emphasized as a stabilization of sympathovagal balance, noted by increased cholingeric and decreased adrenergic modulation of HRV ( 18 ). Seifert et al ( 48 ) found significant age trends of HRV in the group of children under the age of 11 years old (i.e., HRV decreased with increasing age). However, these were not present in the group over the age of 11 years old ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seifert et al ( 48 ) found significant age trends of HRV in the group of children under the age of 11 years old (i.e., HRV decreased with increasing age). However, these were not present in the group over the age of 11 years old ( 48 ). Given that (1) the sample in this study was composed of 13- to 18-year-old athletes and (2) 17- to 18-year olds only made up 5.1% of the total sample, the high performance athletic status, and age range may not have been sensitive enough to capture developmental change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential physiological adaptations, IMT has also been suggested to elicit positive benefits on quality of life (QoL) [15], anxiety and depression in CF adults [17]. Little data is available in children with CF, but a weak correlation between HRV and QoL has been observed in healthy children and adolescents, with suggestions that a stronger correlation would be evident in chronically ill children [54]. Interventions that simultaneously promote improvements in lung function and QoL are highly desirable, especially for those with CF who already face a substantial, time consuming, treatment schedule.…”
Section: Introductionmentioning
confidence: 99%